Convective Heat Transfer During Melting in a Solar LHTES - Mecieb, F. Z.; García Bermejo , F.; Solano Fernández , J. P.; Laouedj, S. (Engineering, Technology & Applied Science Research, 2021)
Melting combined with natural convection in a shell and Latent Thermal Energy Storage (LHTES) tube driven by a solar collector was analyzed numerically in the present work. This work’s particularity lies in the fact that the HTF temperature varies at each moment following the solar irradiance curve. A program (UDF) has been developed and integrated into Ansys to meet this requirement. The use of this coupling strategy allows obtaining realistic unsteady LHTES results. Several numerical investigations were carried out to analyze the effect of the heat sources’ power on the accumulator’s performance. The obtained results show that natural convection considerably influences the heat transfer as well as the melting kinetics of the Phase Change Material (PCM). Besides, the results show that increasing the heat transfer fluid’s thermal load can increase the melting rate of the PCM and the stored energy and reduce the entire melting time.